Factors of positioning and accreditation of cultural agents in a local field of cultural production - Oliva Abarca, Jesús Eduardo (Tarun Tapas Mukherjee, 2017)
This study aimed to analyze the attitudes, skills, and practices, which an aspiring cultural agent must accomplish in order to gain a position in the field of cultural production and to be credited as a functional actor of the art system. The research was limited to the Mexican state of Nuevo León, with the objective of obtaining an overview of the local artistic field from their own actors’ experiences, opinions, and perspectives. The research results demonstrated that the aspiring cultural agents must be capable of fulfilling different roles, being creators, as well as their own promoters and managers at the same time. Also, they must be involved in institutional events in order to be recognized by other cultural agents. Finally, the organization of the local artistic field is defined by intrinsic cultural factors, as well as by extrinsic political and economic circumstances.